2015
DOI: 10.4103/2278-9626.154179
|View full text |Cite
|
Sign up to set email alerts
|

Oral self-care practices, dental attendance and self-perceived oral health status among internal medicine residents in Nigeria

Abstract: Background: Oral health is important for well-being and chronic disease prevention. Physician′s confidence and willingness to counsel patients on lifestyle practices is related to their personal behavior. Limited data exists regarding oral self-care practices among physicians in developing countries, as the majority seeks oral health advice and care from doctors rather than dentists. Aim: To determine the oral self-care practices, dental attendance, and self-perceived oral health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…In the present study, a negative correlation between age and PSR-OHS was found with high significance. This was in concurrence with another study,[ 12 13 14 15 16 17 18 ] which demonstrated that as age advanced among older individuals, the probability of cleaning their teeth twice daily diminished, conversely the younger patients having good oral hygiene, with good periodontal health make them rate their oral health as good.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, a negative correlation between age and PSR-OHS was found with high significance. This was in concurrence with another study,[ 12 13 14 15 16 17 18 ] which demonstrated that as age advanced among older individuals, the probability of cleaning their teeth twice daily diminished, conversely the younger patients having good oral hygiene, with good periodontal health make them rate their oral health as good.…”
Section: Discussionsupporting
confidence: 85%
“…In this study almost all the participants (92.3%) used toothbrush and toothpaste in cleaning their teeth. This is similar to a study done in Lagos and other parts of the world among medical doctors that reported that 99.1% and over 90% of their participants respectively used same [25,26]. In this study, 7.7% of participants used chewing stick in addition to tooth brushes in cleaning their teeth.…”
Section: Discussionsupporting
confidence: 90%
“…In the field of oral health, the recognition and analysis of the process of acquiring individual autonomy is under construction, and studies predominantly show an association between oral self-care and isolated factors. 7,8,9,10,11 The literature points out that appropriate oral health depends on maintaining certain practices, including periodic dental visits, 12,13,14,15 tooth brushing frequency, 7,10,12,16,17 toothbrush replacement frequency, 17,18 dental flossing, and use of auxiliary techniques, 7,12,17,19 and that all these factors together represent oral selfcare. However, the studies usually evaluate oral selfcare in a segmented manner, relating it specifically to dental flossing, toothbrushing or regular visits to the dentist.…”
Section: Introductionmentioning
confidence: 99%